THE ROLE AND PLACE OF UKRAINE IN GLOBAL SUPPLY CHAINS - Marynenko , N. Yu.; Кутко , Т. І. (The actual problems of regional economy development, 2025)
The role and place of Ukraine in global supply chains is studied in the article. Key aspects of the globalization impact on the supply chains’ formation and development are revealed. It is noted that globalization affects the geographical structure, technological base and risk management strategies of modern supply chains, and also poses new challenges to companies, in particular, the need to adhere to the principles of sustainable development, ensuring social responsibility and environmental safety. The dynamics of world trade in goods and services and transport and logistics indicators in the international economic system are analyzed. Data analysis indicates the stable positions of China, the USA and the European Union in world trade, despite global challenges. Changes in the shares of individual countries are due to both macroeconomic factors (pandemic, war, changes in global supply chains) and internal political and economic processes. Ukraine is characterized by a significant decrease in its share in the world trade due to ongoing military operations and their destructive consequences for the economy. It is determined that the key aspects of the world trade’s revival were the activation, digitalization and significant increase in the efficiency of logistics processes due to the introduction of modern information technologies, the integration of digital platforms and the optimization of logistics operations. The positions of the leading countries and Ukraine ae analyzed according to the Logistics Performance Index and the Global Competitiveness Index. It is noted that during 2016–2023, countries such as Germany, Singapore, Sweden, Belgium, the Netherlands and Austria remained stable among the world leaders according to the Logistics Performance Index, which indicates the systematic nature of their approaches to the development of logistics infrastructure, innovative technologies in transportation, improvement of customs procedures and efficiency of freight transportation. Compared with the leading countries of the world, Ukraine’s indicators remain at a rather low level during the period under study. According to the Global Competitiveness Index, the leading countries in 2018-2024 were Singapore, Switzerland, Denmark, Hong Kong, Sweden, and the Netherlands, which built their national economies based on innovative development, the creation of cutting-edge digital infrastructure, stimulating the development of logistics and product supply chains, developing transport infrastructure, etc. In the pre-war period, Ukraine strengthened its position in the ranking. The conditions for realizing Ukraine’s potential in global supply chains in the post-war period have been identified